if y = 2- x then x^2 + 2x(2 - x) = 3 ie x^2 + 4 x -2x^2 = 3 ie 4x - 3 = x^2 x^2 - 4x +3 = 0 = (x - 1)(x - 3) so x = 1 or 3 Check: y= 2 - 1 =1; x^2 = 1, 2xy = 2 x 1 x 1 = 2, 1 +2 = 3. y = 2 - 3 = -1; x^2 = 9, 2xy = 2 x 3 x -1 = -6, 9 + -6 = 3. QED.
That equals 2xy + 3y which factors to y(2x + 3)
L = 3x + 2y
2xy substitute 3 for y and 5 for x 2(5)(3) = 30
xy + xy = 2xy
3x2+6xy+3y2= 3(x2+2xy+y2)= 3(x+y)2
Y=15/(2c+2x)
15xy-2xy-7x+x=13xy-6x
i don't get that if it is 2xy +8 or 8 + 2xy then you can't solve or simplify it any further if it were 8 x 2y then you time the 8 by the 2 to get 16y
x2 + y2 = x2 - 2xy + y2 + 2xy = (x - y)2 + 2xy = 72 + 2*8 = 49 + 16 = 65 You could, instead, solve the two equations for x and y and substitute, but the above method is simpler.
It's an hyperbola equation.
2xy + 6 = 4xyz Divide through by 2: xy + 3 = 2xyz 3 = 2xyz - xy = y*(2xz - x) Therefore, y = 3/(2xz - x) provided that 2xz - x is not zero.
Because 2x+y is addition not multiplication
4x-y2=2xy 2x ? y5 if its plus its 7 xy
2xy + 6xy = 8xy
2xy - 4x plus 8y - 16 equals x plus 4 in parentheses multiplied by 2y minus 4 in parentheses. So, the factors are ( x + 4) and ( 2y - 4) .
2xy=2*30*2=120
-2x - 2y = -122x + 2y = 122y = 12 - 2xy = 6 - x